A Novel Method for High-Level Production of TEV Protease by Superfolder GFP Tag. (12th January 2010) - Wu, Xudong; Wu, Di; Lu, Zhisheng; Chen, Wentao; Hu, Xiaojian; Ding, Yu
Abstract : Because of its stringent sequence specificity, tobacco etch virus (TEV) protease is widely used to remove fusion tags from recombinant proteins. Due to the poor solubility of TEV protease, many strategies have been employed to increase the expression level of this enzyme. In our work, we introduced a novel method to produce TEV protease by using visible superfolder green fluorescent protein ( sf GFP) as the fusion tag. The soluble production and catalytic activity of six variants of sf GFP-TEV was examined, and then the best variant was selected for large-scale production. After purified by Ni-NTA affinity chromatography and Q anion exchange chromatography, the best variant of sf GFP-TEV fusion protease was obtained with purity of over 98% and yield of over 320 mg per liter culture. The sf GFP-TEV had a similar catalytic activity to that of the original TEV protease. Our research showed a novel method of large-scale production of visible and functional TEV protease for structural genomics research and other applications.